Review of Intellectual Assets Principles of CGIAR - CGIAR Independent Evaluation Arrangement (CGIAR Independent Evaluation Arrangement, 2017)
The Intellectual Assests Principles were approved in March 2012. These IA Principles constitute a policy that provides a common position and framework for governing the production, acquisition, management, and dissemination of intellectual assets (IA) and use of Intellectual Property Rights (IPR) with an aim of maximizing global accessibility of CGIAR IA for achieving broadest possible impact on target beneficiaries. The IA Principles (the policy) acknowledge CGIAR’s mandate of generating global public goods for achieving large-scale impact and are intended to further the CGIAR’s Vision: “A world free of poverty, hunger, and environmental degradation”. However, the policy also recognizes that restrictions to global accessibility may be necessary in some cases with more nuanced approaches for managing intellectual assets, including through intellectual property rights and licensing arrangements, for targeting impacts to intended beneficiaries. It sets the conditions for the latter with the aim of serving transparency as well as maximum impact. The policy concerns matters that are critical to the reputation of CGIAR. At the time of the policy’s approval, it was considered to reflect a compromise that “balances trust and Center autonomy with accountability and transparency.” The Review assessed the IA Principles in a comprehensive manner regarding coverage, adequacy, and appropriateness. It assessed the extent to which IA Principles and its implementation have been effective in enhancing efficiency and transparency. The Review found that the implementation of the IA Principles has proceeded systematically with a number of improvements, including a notable increase in legal staffing at each Center, development of a review and oversight process, a robust reporting process and launching of the CGIAR Legal/IP Network (CLIPnet) community of practice. The Review also found some inadequacy of resources and capacity. The review team concluded that the IA Principles were not being used to their full capacity, partly due to inadequate understanding of what the Principles prescribe.